2015
DOI: 10.1515/secm-2013-0121
|View full text |Cite
|
Sign up to set email alerts
|

Melt grafting copolymerization of glycidyl methacrylate onto acrylonitrile-butadiene-styrene (ABS) terpolymer

Abstract: The grafting copolymerization of glycidyl methacrylate (GMA) onto acrylonitrile-butadiene-styrene (ABS) terpolymer was carried out using the melt grafting process. Infrared (IR) spectra, 1 H nuclear magnetic resonance spectra, and elemental analysis results confirmed that GMA was successfully grafted onto the ABS backbone. The grafting occurred at the butadiene region of ABS, and a reaction mechanism has been proposed. The influencing factors of the reaction, such as GMA concentration, the initiator content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Liu et al studied the mechanical properties of blends have been improved by adding elastomers to polyolefins, the study has shown that mechanically mixed recycled polyethylene and polypropylene blends with subsequent elastomers addition display improved mechanical properties, but the amount of elastomer is very large, resulting in appearing a morphology of clear phase separation [11,12]. For another method, free-radical melt grafting of polyolefins has also been studied [13][14][15][16][17][18]. Many studies use maleic anhydride (MAH), silane, glycidyl methacrylate (GMA) and styrene (St) as grafting monomer because of the strong reactivity of the group of them.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al studied the mechanical properties of blends have been improved by adding elastomers to polyolefins, the study has shown that mechanically mixed recycled polyethylene and polypropylene blends with subsequent elastomers addition display improved mechanical properties, but the amount of elastomer is very large, resulting in appearing a morphology of clear phase separation [11,12]. For another method, free-radical melt grafting of polyolefins has also been studied [13][14][15][16][17][18]. Many studies use maleic anhydride (MAH), silane, glycidyl methacrylate (GMA) and styrene (St) as grafting monomer because of the strong reactivity of the group of them.…”
Section: Introductionmentioning
confidence: 99%